Drivers and Traits of Peri–Urbanization in Benin City, Nigeria: A Focus on Ekiadolor Community - Olajuyigbe, Ayo Emmanuel (Advances in Social Sciences Research Journal, 2016)
Peri urban zones are areas capable of promoting urban and rural livelihoods and coping with the pressure and dynamics of population and land use changes. On the other hand, they constitute areas that lead to progressive degradation of the environment and collapse of institutions. This study examined the drivers of growth, characteristics and environmental challenges of the peri urban zones in Benin City, Nigeria using Ekiadolor as a case study. A sample size of 393 amounting to 30% of the total number of building stock in the area was chosen. For the survey, one household per building was selected. A random sampling approach was subsequently adopted to select any available head of household for interview. Some of the attributes investigated included occupation, family size, reasons for staying in the community, length of stay, buildings characteristics, infrastructures, road network and land related issues. The peculiar characteristics of a typical peri-urban community and its asscociated environmental problems were well amplified in Ekiadolor community. It was observed that the establishment of the College of Education and the accompanying employment opportunities was the major driver for the transformation of Ekiadolor to a peri-urban settlement. Other observed drivers include the relatively low housing rents and low cost of land in the community. The study concluded that the establishment of institutions such as universities, colleges of education and research institutes among others outside the immediate precinct of cities could trigger peri – urbanization and therefore recommends that adequate provision should be made in anticipation of the envisaged challenges that are associated with such development. The study further advocated for the creation of a specialized unit to plan and coordinate such settlements. It finally calls for a synergy between the peri – urban communities and the main cities through progressive integration.